Hubungan antara Disiplin dan Motivasi Belajar dengan Kemandirian Belajar Siswa di SMA Negeri 1 Binjai - Muhammad Faisal Situmorang; Syaiful Akhyar Lubis; Azhar Aziz (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
Learning independence is the ability of a student in realizing his will or desire in a way without dependent on others. This study aims to determine the relationship between learning discipline and learning motivation with the independence of student learning in SMA Negeri 1 Binjai. This research is quantitative research with population as much as 324 students of SMA Negeri 1 Binjai. By using stratified random sampling technique obtained sample of 180 respondents. Data analysis technique using Multiple Regression Analysis. In general, discipline, motivation to learn, and independence of high school students learn 1 Binjai classified high. The results showed that in the first hypothesis there is a positive and significant correlation between discipline with student learning independence in SMA Negeri 1 Binjai with correlation coefficient of 0.730 and p 0.000, then the second hypothesis shows that there is a positive and significant relationship between learning motivation with independence student learning, with correlation coefficient of 0.751 and p 0.000 and in the third hypothesis showed that there is a positive and significant relationship between discipline and learning motivation with learning independence with a correlation coefficient of 0.793 and p 0.000. The total effective contribution between the learning discipline and the learning motivation toward the independence of the students of SMA Negeri 1 Binjai is 62.8%.